Anaplastic Lymphoma Kinase-Positive Lung Cancer with Mucoepidermoid Carcinoma Differentiation: A Case Report - Sakatani, Toshio (Case Rep Oncol, 2020)
Mucoepidermoid carcinoma (MEC) of the lung is an extremely rare tumor, and a standard chemotherapy has not been established. Furthermore, little work has been conducted on the genetic characteristics of MEC. We herein report the case of a 42-year-old nonsmoking male patient who was referred to our hospital due to cough. Chest computed tomography demonstrated infiltration and atelectasis in the right lower lobe. He was eventually diagnosed with non-small cell lung cancer (NSCLC) with MEC differentiation corresponding to clinical stage IVA (cT4N2M1a[PLE]). Genetic testing for EGFR mutations was negative, but positive for anaplastic lymphoma kinase (ALK) fusion gene. After 2 weeks of first-line treatment with alectinib, the tumor decreased in size and his symptoms improved. Advanced MEC is a rare tumor, and reports on the treatment of ALK-positive NSCLC with MEC differentiation are rare.